The dynamics of indecision : a failure of leadership - Roberto, Michael A. (FT Press Delivers elements., 2011)
"This Element is an excerpt from Why Great Leaders Don't Take Yes for an Answer: Managing for Conflict and Consensus (ISBN: 9780131454392) by Michael A. Roberto. Why so many organizations fall into the trap of 'endless talk and no action'-and how to escape that trap, decide, and move forward!"--Resource description page.